(RETRACTION) KOMPETENSI DOSEN PENDIDIKAN JASMANI PADA MASA PANDEMI COVID-19 DI IAIN SALATIGA - Amanda Syukriadi; Fatkhur Rozi (Jurnal Dinamika Pendidikan, 2021)
Evaluation is needed for physical education lectures at IAIN Salatiga. The purpose of this study is the performance education of physical education lecturers at IAIN Salatiga on pedagogical, professional, personality, and social competencies. This research method is descriptive quantitative research with a survey approach using an online questionnaire. The population of this study was IAIN Salatiga students who attended physical education lectures in the odd semester of 2020/2021. The sample of this study was 114 students who were selected using the simple random sampling technique. The results showed that the level of pedagogical competence of physical education lecturers at IAIN Salatiga in the excellent category was 34.2%, 61.4% good, and 4.4% sufficient. For professional competence in the excellent category, the number was 39.5%, 53.5% good, and 7.0% sufficient. Furthermore, personality competence in the excellent category was 25.4%, 65.8% good, and 8.8% sufficient. As for the social competence in the excellent category was 18.4%, 72.8% good, and 8.8% sufficient. This research concludes that physical education lecturers at IAIN Salatiga are in good categories for pedagogical, professional, personality, and social competencies with a mean value of 63.38%. The suggestion of this research is that physical education lecturers at IAIN Salatiga always improve their performance in teaching.